Parasitoids of Hesperiidae from peninsular India with description of a new species of Dolichogenidea (Hymenoptera: Braconidae) parasitic on caterpillar of Borbo cinnara (Wallace) (Lepidoptera: Hesperiidae) - Gupta, Ankita; Lokhande, Swapnil A.; Soman, Abhay (Zootaxa, 2013)
Five species of parasitic wasps associated with hesperiids from peninsular India are documented along with the description of a new species of gregarious endoparasitoid, Dolichogenidea cinnarae sp. nov. (Hymenoptera: Braconidae) parasitic on caterpillar of Borbo cinnara (Wallace) (Lepidoptera: Hesperiidae). Also, the gregarious larval parasitoid, Cotesia erionotae (Wilkinson) (Braconidae) and solitary pupal parasitoid Charops plautus Gupta & Maheshwary (Ichneumonidae) were bred from the host Udaspes folus (Cramer) on the host plant Hedychium coronarium J. Koenig. Udaspes folus is the new host record for the parasitic wasp genus Charops. Cotesia erionotae was bred from U. folus caterpillars from three states: Maharashtra, Karnataka and Kerala. An encyrtid wasp Ooencyrtus papilionis Ashmead was bred from eggs of Bibasis jaina (Moore) on the host pant Hiptage benghalensis (L.). This is the first documentation of a parasitic wasp from the genus Bibasis. Leptobatopsis indica (Cameron) (Ichneumonidae), often associated with Parnara guttatus (Bremer & Grey), was recorded from the Andaman islands.